2020
DOI: 10.4314/br.v18i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Enterobacteriaceae producing β-lactamase and methicillin-resistant staphylococci isolated from the hospital environment and catheters in two public hospitals in Benin, Republic of Benin

Abstract: Antimicrobial resistance is a real public health problem. All over the world, it has a considerable impact in hospitals. The present study was conducted to ascertain the bacterial ecology in two hospitals in Benin as well as the resistance genes present in the recovered isolates. A total of 146 environmental and catheter samples were collected at the University Hospital Center of Abomey-Calavi / So-Ava and at the Beninese Army Hospital of Cotonou. These samples were inoculated on Mannitol Salt and Eosin Methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Although studies have reported the presence of ESBL-producing bacteria and their resistance genes in various samples from Africa and globally (7,(20)(21)(22)(23), limited data exist on the prevalence of ESBLproducing Enterobacterales in healthy pregnant women, the food chain, and the environment in Benin (21,(24)(25)(26)(27)(28). Therefore, the present study investigates the prevalence and characteristics of ESBLproducing E. coli in healthy pregnant women, the hospital environment, and the food chain within various tertiary hospitals in Benin.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have reported the presence of ESBL-producing bacteria and their resistance genes in various samples from Africa and globally (7,(20)(21)(22)(23), limited data exist on the prevalence of ESBLproducing Enterobacterales in healthy pregnant women, the food chain, and the environment in Benin (21,(24)(25)(26)(27)(28). Therefore, the present study investigates the prevalence and characteristics of ESBLproducing E. coli in healthy pregnant women, the hospital environment, and the food chain within various tertiary hospitals in Benin.…”
Section: Introductionmentioning
confidence: 99%